THE PREVALENCE OF ANTIPHOSPHOLIPID ANTIBODIES AND THEIR CORRELATION WITH CLINICAL, LABORATORY FINDINGS IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS - Khuc, Thi Tai Linh; Le, Dinh Tung; Bui, Van Dan (Tạp chí Sinh lý học Việt Nam, 2023)
Objective: To evaluate the prevalence of antiphospholipid antibodies (aPL Abs) in patients with systemic lupus erythematosus (SLE) and the relationship between these antibodies and clinical and laboratory findings. Methods: A cross-sectional descriptive study was conducted on 60 patients newly diagnosed with SLE according to the SLICC 2012 criteria at the Center for Allergy - Clinical Immunology, Bach Mai Hospital, from October 2022 to August 2023. The aPL-positive group was defined as patients who tested positive for at least one antiphospholipid antibody. Clinical manifestations and laboratory findings were compared between the aPL-positive and aPL-negative groups. Results: Among the 60 patients, 37 (61.67%) tested positive for at least one aPL antibody. The proportions of patients positive for single antibodies were 46.67% for anticardiolipin antibody (aCL), 30% for lupus anticoagulant (LAC), 20% for anti-β2 glycoprotein I antibody (β2GPI), and 11.67% for aPL; 35% of patients were positive for double antibodies, and 18.33% were positive for triple antibodies. Positive aPL and LAC antibodies were significantly associated with chronic kidney disease compared with the negative group. However, no significant differences were found between the two groups regarding hematological manifestations, neurological manifestations, thromboembolism, obstetric pathology, or livedo. Conclusion: A total of 61.7% of newly diagnosed SLE patients were positive for at least one antiphospholipid antibody, and the presence of these antibodies was independently associated with an increased risk of chronic kidney disease in patients with SLE.